Implementasi Penggunaan LkKPD Energi Terbarukan Berbasis Inkuiri untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Nia Sintiawati; Rudi Haryadi; Ganesha Antarnusa (Smart Education, 2024)
Abstract: One of the factors causing low student learning outcomes is the teacher's inability to create exciting learning and appropriate teaching materials. Therefore, researchers developed teaching materials as inquiry-based learner worksheets with renewable energy materials. This research aims to determine the appropriateness of the learner worksheets being developed and their influence on improving students' critical thinking abilities. This research uses a development approach or Research and Development. The learning model is ADDIE. In the implementation stage, one group pretest-posttest experimental design was used. This research results in the learner worksheet being developed in printed form. The results of the quantitative data are the validator value for learner worksheets, with an average of 83.5%, which is a very feasible category. The results of the quantitative data analysis are average values with sig. 0.138 is normally distributed, the homogeneity value is 0.137, which is homogeneous, and the hypothesis value is 0.000, which means H0 is accepted and H1 is rejected. The N-gain value is 0.42 in the medium category. The analysis of student responses showed that 33% strongly agreed, 63% agreed, 3% disagreed, and 1% disagreed. So, it can be concluded that the learner worksheets are suitable for use and have an effect on improving students' critical thinking skills.Keywords: inquiry learning; learner worksheet.Â Abstrak: Faktor rendahnya hasil belajar siswa salah satunya disebabkan oleh ketidakmampuan seorang guru dalam menciptakan pembelajaran yang menarik serta bahan ajar yang tepat. Oleh karena itu, dikembangkan bahan ajar berupa LKPD berbasis inkuiri dengan materi energi terbarukan. Tujuan penelitian ini yaitu untuk mengetahui tingkat kelayakan LKPD yang dikembangkan dan pengaruhnya terhadap peningkatan kemampuan berpikir kritis siswa. Penelitian ini menggunakan pendekatan pengembangan Research and Development. Model pembelajaran yang digunakan yaitu ADDIE. Dalam tahap implementasi menggunakan desain eksperimen one group pretest-posttest design. Hasil dari penelitian ini adalah LKPD yang dikembangkan berbentuk cetak. Hasil data kuantitatif yaitu nilai validator terhadap LKPD dengan rata-rata 83,5% dengan kategori sangat layak. Hasil analisis data kuantitatif berupa nilai normalitas dengan sig. 0,138 berdistribusi normal, nilai homogenitas 0,137 yang bersifat homogen, nilai hipotesis 0,000 yang berarti H0 diterima dan H1 ditolak, dan nilai N-gain 0,42 dengan kategori sedang. Hasil analisis respon siswa menyatakan 33% sangat setuju, 63% setuju, 3% kurang setuju, dan 1% tidak setuju. Dapat disimpulkan bahwa LKPD layak digunakan dan berpengaruh pada peningkatan kemampuan berpikir kritis siswa.Kata kunci: LKPD; Pembelajaran Inkuiri; Energi Terbarukan